The Correlation Among Self-Confidence, Vocabulary Size, And Speaking Performance of EFL Students at IAIN Palangka Raya - Harisa, Nor (Journal Of Foreign Language Learning and Teaching, 2021)
The study is aimed at measuring the correlation among self confidence ,vocabulary size and speaking speaking performance of the Efl students at IAIN Palangka Raya. The design of the study was correlational design. The population of this research was 68 English students of fifth semester academic